Mechanistic Probing of Encapsulation and Confined Growth of Lithium Crystals in Carbonaceous Nanotubes. Issue 51 (15th October 2021) - Wei, Ping; Cheng, Yong; Yan, Xiaolin; Ye, Weibin; Lan, Xiangna; Wang, Lina; Sun, Jingjie; Yu, Zhiyang; Luo, Guangfu; Yang, Yong; Rummeli, Mark H.; Wang, Ming‐Sheng
Abstract: Encapsulation of lithium in the confined spaces within individual nanocapsules is intriguing and highly desirable for developing high‐performance Li metal anodes. This work aims for a mechanistic understanding of Li encapsulation and its confined growth kinetics inside 1D enclosed spaces. To achieve this, amorphous carbon nanotubes are employed as a model host using in situ transmission electron microscopy. The carbon shells have dual roles, providing geometric/mechanical constraints and electron/ion transport channels, which profoundly alter the Li growth patterns. Li growth/dissolution takes place via atom addition/removal at the free surfaces through Li + diffusion along the shells in the electric field direction, resulting in the formation of unusual Li structures, such as poly‐crystalline nanowires and free‐standing 2D ultrathin (1–2 nm) Li membranes. Such confined front‐growth processes are dominated by Li {110} or {200} growing faces, distinct from the root growth of single‐crystal Li dendrites outside the nanotubes. Controlled experiments show that high lithiophilicity/permeability, enabled by sufficient nitrogen/oxygen doping or pre‐lithiation, is critical for the stable encapsulation of lithium inside carbonaceous nanocapsules. First‐principles‐based calculations reveal that N/O doping can reduce the diffusion barrier for Li + penetration, and facilitate Li filling driven by energy minimization associated with the formation of low‐energy Li/C interfaces. Abstract : Lithium encapsulation and its confined growth kinetics in amorphous carbon nanotubes (aCNTs) are studied using in situ transmission electron microscopy. The carbon shells play dual roles, providing geometric/mechanical constraints and electron/ion transport channels, which profoundly alter the Li growth patterns, resulting in unusual Li nanostructures. Importantly, it is revealed that sufficient nitrogen/oxygen doping is critical for aCNTs to reliably encapsulate lithium.